2020
DOI: 10.1101/2020.05.01.071092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex-dependent effects of chronic intermittent voluntary alcohol consumption on attentional, not motivational, measures during probabilistic learning and reversal

Abstract: BackgroundForced alcohol (ethanol, EtOH) exposure has been shown to cause significant impairments on reversal learning, a widely-used assay of cognitive flexibility, specifically on fully-predictive, deterministic versions of this task. However, previous studies have not adequately considered voluntary EtOH consumption and sex effects on probabilistic reversal learning. The present study aimed to fill this gap in the literature.MethodsMale and female Long-Evans rats underwent either 10 weeks of voluntary inter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…After one week of post-surgery recovery, rats began the stimulus-based discrimination learning task (Figure 1B). This task was described in detail previously (Aguirre et al, 2020;Harris et al, 2020), however, in the present design we assigned deterministic stimulus-reward assignments -correct (100%) vs incorrect (0%). Rats initiated each trial by nosepoking a white graphic stimulus in the center screen (displayed for 40 s).…”
Section: Stimulus-outcome Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…After one week of post-surgery recovery, rats began the stimulus-based discrimination learning task (Figure 1B). This task was described in detail previously (Aguirre et al, 2020;Harris et al, 2020), however, in the present design we assigned deterministic stimulus-reward assignments -correct (100%) vs incorrect (0%). Rats initiated each trial by nosepoking a white graphic stimulus in the center screen (displayed for 40 s).…”
Section: Stimulus-outcome Learningmentioning
confidence: 99%
“…A causal investigation of their interaction in stimulus-based and actionbased learning in rodents is lacking in the broader literature. Further, we recently suggested that a thorough consideration of both accuracy and speed of response during learning may be particularly informative when identifying neural signatures of flexible learning (Aguirre et al, 2020;Harris et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Compulsive HD animals exhibited decreased sensitivity to positive feedback compared with LD animals, showing decreased conditional win-stay probability (i.e., the probability of pressing the same lever rewarded in the previous trial). The insensitivity to reward contingencies has also been shown in different preclinical models of compulsive-like behavior: first, compulsive HD rats selected by SIP exhibited insensitivity to reinforcer devaluation and excessive habit formation measured by similar lever pressing under extinction after the consumption of either a different reinforcer or the same reinforcer compared with LD rats (Merchán et al, 2019); second, the rats exposed to chronic intermittent voluntary alcohol consumption, a model of alcohol use disorder, used win-stay strategy less than H 2 Odrinking rats (Aguirre et al, 2020); third, the animals exposed to alternation of a standard chow with a high palatable diet, a model of compulsive eating behavior, showed reduced sensitivity to d-amphetamine, suggestive of a hypofunctional reward system (Moore et al, 2020); and fourth, transgenic SAPAP3 −/− mice showed lower response rates and fewer attempts to collect food pellets in schedules of reinforcement tasks than wild-type mice, indicating altered reward processing (Ehmer et al, 2020). Finally, mirtazapine, an antidepressant with specific serotonergic effects, significantly increased the sensitivity to positive feedback, increasing the proportion of the win-stay strategy on the PSRL (Drozd et al, 2019).…”
Section: Increased Cognitive Impulsivity In Compulsive Hd Rats Select...mentioning
confidence: 92%